Ventilation Management and Outcomes for Subjects With Neuromuscular Disorders Admitted to ICUsWith Acute Respiratory Failure. - Chabert, Paul; Bestion, Audrey; Fred, Abla-Akpene; Schwebel, Carole; Argaud, Laurent; Souweine, Bertrand; Darmon, Michael; Piriou, Vincent; Lehot, Jean-Jacques; Guérin, Claude (Respiratory Care, 2021)
BACKGROUND: Patients with neuromuscular disorders (NMD) share the risk of acute respiratory failure (ARF) leading to ICU admissions. Noninvasive ventilation (NIV) is often proposed as an alternative to invasive ventilation. This study describes clinical features, ventilation management, and outcomes of subjects with NMD admitted to ICU and managed for ARF. METHODS: We performed a multicenter retrospective study in 7 adult ICUs in the Auvergne-Rhone-Alpes area in France involving subjects with NMD admitted to the ICU for ARF. The primary end point was ICU mortality. Secondary end points were NIV failure, weaning from invasive ventilation, and long-term mortality. We hypothesized a poorer outcome in the case of bulbar musculature involvement. RESULTS: A total of 242 subjects were included; 142 subjects had nonhereditary NMD (58.7%), and 100 had hereditary NMD (41.3%). Eleven subjects had home ventilation through a tracheostomy. While 112 were intubated at admission, 119 initially underwent NIV. NIV was successful in avoiding orotracheal intubation in 78 subjects (65.5%). ICU mortality was 13.6%. Factors associated with ICU mortality were nonhereditary NMD and requirement for invasive ventilation. The involvement of bulbar musculature in ARF and hereditary NMD were associated with NIV failure. After a median follow-up of 1.2 y, 53 of 209 subjects had died. CONCLUSIONS: The ICU mortality of NMD subjects with ARF was low, with no impact of bulbar muscles involvement. NIV was proposed for approximately half of the subjects, and it was more effective when ARF was not attributed to bulbar musculature involvement. The long-term outcome was good.